Placement of Entries, Phono-morphological Information and Emotive Idioms in Al-`Inarah Al-Tahzibiyyah Kamoes Arab-Melajoe - Basuni Imamuddin (Sunan Kalijaga: International Journal of Islamic Civilization, 2019)
In Indonesia there are two kinds of bilingual Arabic-Malay dictionaries and 26 Arabic-Indonesian dictionaries (1925-2018), but all refer to the Dictionary of Al-`Inārah Al-Thżībiyyah Kamoes Arab Melajoe by H. Moehammad Fadloellah and B.Th. Brondgeest (1925). Based on research (Imamuddin, 2017), the placement of entries and subentries is often not consistent. Therefore, there is an urgency to research and revise the dictionary which is the "parent" of the 28 dictionaries. It is expected that the 28 dictionaries can be updated so that inaccuracies can be avoided. To propose research and revisions to the "parent" work, the factors analyzed are entries and subentries. Phonological information is given to readers so that they know the changes that occur in a word. Al-`Inārah provides this information. Morphological information also provides an explanation of the origin of words in Arabic. Therefore, the analysis will be accompanied by the book entitled Syaza Al-Urf fi Fan Al-Sharf (1980). Idiomatic structure is also presented by the author so that the reader knows that certain verbs must also be accompanied by certain prepositions.